Gemigliptin Attenuates Renal Fibrosis Through Down-Regulation of the NLRP3 Inflammasome - Seo, Jung Beom (Diabetes Metab J, 2019)
BACKGROUND: The hypoglycemic drugs dipeptidyl peptidase-4 (DPP-4) inhibitors have proven protective effects on diabetic kidney disease, including renal fibrosis. Although NOD-like receptor protein 3 (NLRP3) inflammasome activation is known to play an important role in the progression of renal fibrosis, the impact of DPP-4 inhibition on NLRP3-mediated inflammation while ameliorating renal fibrosis has not been fully elucidated. Here, we report that the renoprotective effect of gemigliptin is associated with a reduction in NLRP3-mediated inflammation in a murine model of renal fibrosis. METHODS: We examined the effects of gemigliptin on renal tubulointerstitial fibrosis induced in mice by unilateral ureteral obstruction (UUO). Using immunohistochemical and Western blot analysis, we quantitated components of the NLRP3 inflammasome in kidneys with and without gemigliptin treatment, and in vitro in human kidney tubular epithelial human renal proximal tubule cells (HK-2) cells, we further analyzed the effect of gemigliptin on transforming growth factor-β (TGF-β)-stimulated production of profibrotic proteins. RESULTS: Immunohistological examination revealed that gemigliptin ameliorated UUO-induced tubular atrophy and renal fibrosis. Gemigliptin-treated kidneys showed a reduction in levels of NLRP3, apoptosis-associated speck-like protein containing a caspase recruitment domain (ASC), caspase-1, and interleukin-1β, which had all been markedly increased by UUO. In line with the in vivo results, TGF-β markedly increased NLRP3 inflammasome markers, which were attenuated by gemigliptin treatment. Furthermore, gemigliptin treatment attenuated phosphorylated nuclear factor-κB levels, which had been increased in the UUO kidney as well as in TGF-β-treated cultured renal cells. CONCLUSION: The present study shows that activation of the NLRP3 inflammasome contributes to UUO-induced renal fibrosis and the renoprotective effect of gemigliptin is associated with attenuation of NLRP3 inflammasome activation.